IGF2BP2 Shapes the Tumor Microenvironment by Regulating Monocyte and Macrophage Recruitment in Bladder Cancer - Jianpeng Li; Yunzhong Jiang; Minghai Ma; Lu Wang; Minxuan Jing; Zezhong Yang; Lizhao Wang; Quanpeng Qiu; Rundong Song; Yuanchun Pu; Yuanquan Zhang; Nan Mei; et al. (Cancer Medicine)
ABSTRACT Background Immunotherapy has shown promise for bladder cancer (BC) treatment but is effective only in a subset of patients. Understanding the tumor microenvironment (TME) and its regulators, such as the expression of N6‐methyladenosine (m6A) regulators, may improve therapeutic outcomes. This study focuses on the role of IGF2BP2, an m6A reader, in modulating the BC TME. Methods Transcriptomic and single‐cell RNA‐seq data from public databases were analyzed to identify BC subgroups and investigate IGF2BP2's role in the TME. Clustering and PCA identified key m6A regulators. NicheNet and SCENIC analyses were used to predict cell–cell interactions and transcriptional regulators, respectively. IGF2BP2's role in macrophage recruitment was validated via co‐culture experiments and RNA sequencing. Results Unsupervised clustering identified BC subgroups with distinct TME characteristics, with IGF2BP2 emerging as a key regulator associated with poor prognosis and reduced response to immunotherapy. Single‐cell analysis revealed IGF2BP2's high expression in the GE‐9 epithelial subpopulation, characterized by immune evasion features and cytokine‐mediated macrophage recruitment. NicheNet analysis showed that GE‐9 cells interact with monocyte/macrophage populations through cytokine signaling. Co‐culture experiments confirmed IGF2BP2's role in recruiting macrophages, partially mediated by CCL2. Furthermore, IGF2BP2 expression was linked to immunosuppressive M2‐like and SPP1+ macrophages, contributing to an angiogenesis‐promoting and immunosuppressive TME. Conclusion IGF2BP2 shapes the BC TME by modulating macrophage infiltration and polarization, leading to an immunosuppressive microenvironment that hinders immunotherapy. Targeting IGF2BP2 could enhance the efficacy of current therapies and improve patient outcomes.